Pengaruh Penggunaan Media Puzzle Terhadap Kemampuan Kognitif Anak Usia Dini Usia 5-6 tahun di PAUD Sentuhan Kasih Abadi Tarutung - Sharlin Elviyana Harefa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to determine the effect of number puzzles on the arithmetic cognitive abilities of early childhood. The research hypothesis was: "Number Puzzles have an effect on improving the cognitive abilities of early childhood at the Sentuhan Kasih Abadi Preschool, GBI Tarutung." The population was 80 children aged 5-6 years (group B) at the Sentuhan Kasih Abadi Preschool, GBI Tarutung. The study sample was determined using a nonprobability sampling technique: 20 students from Pondok Daud class served as the experimental class using number puzzles and 20 students from Judea class served as the control class using conventional treatment. The research method used was a Quasi-Experimental design with a Nonequivalent Control Group Design. The instrument used in this study was a questionnaire item of 20 items. The research data for the questionnaire was analyzed using the average difference test formula (N-Gain Score) it was found that the average value for the experimental class was 0.7662 in the high category. And the average value for the control class was 0.1430 in the low category. Then conducting an independent test using the t test obtained the value thitung = 11,940 > ttabel(α=0,05; df=38) = 2,021 Thus it can be concluded that the research hypothesis is accepted, namely the number puzzle media has an effect on improving the cognitive abilities of early childhood children in PAUD Sentuhan Kasih Abadi GBI Tarutung and H0 is rejected.